Imaging of the degenerative spine using a sagittal T2-weighted DIXON turbo spin-echo sequence. Issue 131 (October 2020) - Sollmann, Nico; Mönch, Sebastian; Riederer, Isabelle; Zimmer, Claus; Baum, Thomas; Kirschke, Jan S.
Highlights: This study investigates if fat-only images of DIXON sequences can replace conventional T1-weigthed imaging. Patients with lumbar back pain due to suspected degenerative disease were enrolled. No difference in diagnostic yield between fat-only images and conventional T1-weighted imaging was detected. DIXON sequences might be sufficient in clinical practice to accurately detect degenerative changes. Abstract: Purpose: To evaluate the diagnostic performance of a sagittal T2-weighted DIXON turbo spin-echo (TSE) sequence and to assess whether fat-only images could replace dedicated sagittal T1-weighted sequences for magnetic resonance imaging (MRI) of the degenerative spine. Method: 35 patients (56.5 ± 19.8 years, 62.9 % males) with lumbar back pain (LBP) who underwent MRI of the lumbar spine including a sagittal T2-weighted DIXON sequence (acquisition time: 3:25 min) and T1-weighted sequence (acquisition time: 3:03 min) were included. Two image layouts (layout 1: fat-only AND water-only AND in-phase images of the DIXON sequence; layout 2: water-only AND in-phase images of the DIXON sequence AND T1-weighted images) were evaluated by two readers (R1 and R2) concerning degenerative changes including diagnostic confidence (1 – low, 2 – intermediate, and 3 – high) and signal changes of vertebral bone marrow (BM). Results were compared between readers and layouts. Results: No differences were observed in the number of detected pathologies on a segment-wise level, nor in the number of segments affected by degenerative changes when comparing evaluations of layout 1 and layout 2 for each reader. Diagnostic confidence was high without a statistically significant difference between the readings of both layouts (R1: layout 1: 2.79 ± 0.41, layout 2: 2.81 ± 0.39, p = 0.53; R2: layout 1: 2.99 ± 0.07, layout 2: 2.99 ± 0.07, p = 0.99). Conclusions: In patients with LBP, MRI using a sagittal T2-weighted DIXON sequence and no separate T1-weighted sequence might be sufficient to accurately detect common degenerative changes with high diagnostic confidence. Sparing dedicated T1-weighted sequences can considerably reduce overall scan time.